2018
DOI: 10.1371/journal.pone.0196764
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and cervical cancer survival of Indigenous and non-Indigenous Australian women: A semi-national registry-based cohort study (2003-2012)

Abstract: BackgroundLittle is known about the impact of comorbidity on cervical cancer survival in Australian women, including whether Indigenous women’s higher prevalence of comorbidity contributes to their lower survival compared to non-Indigenous women.MethodsData for cervical cancers diagnosed in 2003–2012 were extracted from six Australian state-based cancer registries and linked to hospital inpatient records to identify comorbidity diagnoses. Five-year cause-specific and all-cause survival probabilities were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
7
10
0
Order By: Relevance
“…Cervical cancer patients who had comorbidity were 1.58 times at high risk to develop the event than those who haven’t comorbidity in this study. This is in agreement with the studies conducted in Australian [HR = 4.6,95% (CI: 3.54–6.03)] [27] and Ethiopia [HR = 2.02, 95% CI: 1.01–4.05) [23]. The study on HIV infection and survival among women with cervical cancer in Botswana indicated that HIV infection significantly increased the risk for death among all women with cervical cancer [HR = 1.95;95%CI(1.20 to 3.17)] [28] and this also strengthen the current study result since prevalence of HIV infection from comorbidity lists was the highest.…”
Section: Discussionsupporting
confidence: 93%
“…Cervical cancer patients who had comorbidity were 1.58 times at high risk to develop the event than those who haven’t comorbidity in this study. This is in agreement with the studies conducted in Australian [HR = 4.6,95% (CI: 3.54–6.03)] [27] and Ethiopia [HR = 2.02, 95% CI: 1.01–4.05) [23]. The study on HIV infection and survival among women with cervical cancer in Botswana indicated that HIV infection significantly increased the risk for death among all women with cervical cancer [HR = 1.95;95%CI(1.20 to 3.17)] [28] and this also strengthen the current study result since prevalence of HIV infection from comorbidity lists was the highest.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to previous reports from Europe, we observed an increase in cervical cancer mortality with age, particularly in women aged 65 years and older . These findings call for action, particularly because women aged 65 years and older are not recommended for screening for cervical cancer in the majority of European countries, including Denmark.…”
Section: Discussionsupporting
confidence: 88%
“…The high mortality in older women may be a result of a high proportion of advanced stage disease, 18,19 high comorbidity 15 Unfortunately, we had no information on treatment or refusal thereof in the present study and therefore we cannot tell whether the high mortality rate among older women may to some extent be due to older women being less likely to accept and adhere to standard treatment. 21 In the present study, the hysterectomy-corrected cervical can- 19 we cannot rule out that the proportion of women with advanced-stage disease may have been higher prior to 2005, which would explain the temporal decline in mortality rates.…”
Section: Re Sultsmentioning
confidence: 81%
See 2 more Smart Citations